One‐Step Controllable Synthesis of Mesoporous MgCo2O4 Nanosheet Arrays with Ethanol on Nickel Foam as an Advanced Electrode Material for High‐Performance Supercapacitors. Issue 56 (7th September 2018) - Teng, Yifei; Li, Yingdi; Zhang, Ziqing; Yu, Deyang; Feng, Yi; Meng, Yanan; Tong, Wenming; Wu, Yunpeng; Zhao, Xudong; Liu, Xiaoyang
Abstract: In recent years, ternary transition metal oxides (TTMOs), especially spinel type TTMOs have attracted widespread attention as promising candidates for electrode materials. Among all of the popular TTMOs, MgCo2 O4 is an outstanding one, owing to its superior theoretical capacitance. In this work, MgCo2 O4 nanosheet arrays (NSAs) grown directly on nickel foams were fabricated through a facile hydrothermal process at 120 °C for 4 h. With a series of structural and morphological characterization techniques, it was found that the ethanol played a key role in controlling the composition and morphology during the synthesis process. The MgCo2 O4 NSAs exhibited a superior specific capacitance of 853.06 C g −1 (at 1 mA cm −2 ) and enhanced cycling performance, with 94.65 % of initial capacitance retained after 3000 cycles when used as a binder‐free integrated electrode for electrochemical supercapacitors; much higher than other reported data for MgCo2 O4 as well. The excellent electrochemical properties mainly came from the unique morphology of the MgCo2 O4 NSAs. This study will demonstrate the applications of MgCo2 O4 NSAs based large‐scale supercapacitors grown on low‐cost nickel foams. Abstract : Foam party : MgCo2 O4 nanosheet arrays have been prepared on a Ni foam substrate through a facile one‐step hydrothermal method and used as a binder‐free electrode material for supercapacitors. The MgCo2 O4 NSAs electrode exhibits an electrochemical capacitance up to 853.06 C g −1 (at 1 mA cm −2 ) and about 94.65 % of the capacitance was retained after 3000 cycles (at 10 mA cm −2 ).